2022
DOI: 10.30773/pi.2022.0174
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Social Brain Network Topology at Rest in Children With Autism Spectrum Disorder

Abstract: Objective Underconnectivity in the resting brain is not consistent in autism spectrum disorder (ASD). However, it is known that the functional connectivity of the default mode network is mainly decreased in childhood ASD. This study investigated the brain network topology as the changes in the connection strength and network efficiency in childhood ASD, including the early developmental stages.Methods In this study, 31 ASD children aged 2–11 years were compared with 31 age and sex-matched children showing typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…This pattern is potentially present in early childhood, as a recent study by Yoon et al (2022) found lower network efficiencies and reduced longer-range anterior-posterior resting-state connectivity in 2-6 year-olds with ASD [13]. Results from functional connectivity studies led to the development of a cortical underconnectivity theory, which postulated that the observed differences resulted from a deficiency in the presence or function of longer-range distal connections and an overreliance on shorter-range or local connections [15][16][17].…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…This pattern is potentially present in early childhood, as a recent study by Yoon et al (2022) found lower network efficiencies and reduced longer-range anterior-posterior resting-state connectivity in 2-6 year-olds with ASD [13]. Results from functional connectivity studies led to the development of a cortical underconnectivity theory, which postulated that the observed differences resulted from a deficiency in the presence or function of longer-range distal connections and an overreliance on shorter-range or local connections [15][16][17].…”
Section: Introductionmentioning
confidence: 70%
“…A mega-analysis of nearly 2,000 individuals between 5-58 years old found that hypoconnectivity of the sensory and attentional network and hyperconnectivity between cortical and subcortical systems were associated with clinically relevant autistic features such as social impairments, repetitive behavior, and sensory processing 11 . This pattern is potentially present in early childhood, as a recent study by Yoon et al (2022) found lower network efficiencies and reduced longer-range anterior-posterior resting-state connectivity in 2-6 year-olds with ASD…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similar to our results, one study showed no significant differences in the global topological properties within the DMN of children with ASD compared to children with TD (Chen et al, 2021). While another study reported a lower local efficiency reduction and higher global efficiency in brain networks of children and adolescents with ASD (Rudie et al, 2012; Yoon et al, 2022). In addition, (Alaerts et al, 2015) found a reduced global and local efficiency of the ASD group, suggesting that the brain network in ASD has underconnectivity, and disrupted efficiency.…”
Section: Discussionmentioning
confidence: 97%